Economic and social impacts of Web3 and the metaverse in the Global South - Nir Kshetri (International Telecommunications Society (ITS), 2023)
Individuals and organizations in the global south are participating at an increasing rate in Web3 and the metaverse economies. This paper gives an overview of the key benefits to these economies that stem from Web3 and the metaverse. It provides a perspective on the global south's preparedness to benefit from Web3 and the metaverse looking at key indicators related to the adoptions of cryptocurrency, and Web3 browser and investment in Web3 and the metaverse. It provides details of economic and social impacts of the metaverse in key areas. The paper talks about the role of the metaverse economy as a job creator. It also reviews the metaverse's effects on training, education, and knowledge exchange, innovation and entrepreneurship. It will discuss how the metaverse can help the global south internationalize cultural products and artifacts. It analyses how Web3 can provide leapfrogging opportunity in areas such as finance. It also considers the roles of Web3 in dealing with emergencies, crisis and humanitarian intervention. This paper also explains how various trust issues can be addressed by Web3, which is especially important in the context of the global south due to low levels of trust and high costs of intermediation. It highlights some challenges that the global south needs to overcome to realize the full benefits of Web3 and the metaverse.
Keywords: 330; global south; leapfrogging; metaverse; P2E games; Web3